O impacto do uso de indicadores de performance: um estudo de caso na logística de líquidos - Santana, Claudio José de (2004)
On this globalized world where to adapt to changes is as importani as to produce, to distribute and to seu, using performance indicators is a fundamental tool, so that corporations can identify and elirninate its acting gaps, becoming more efficient and productive. This study case has as objective to identify benefits and threats found in the use of the operational performance indicators, in the logistics area of an industrial company. The case was based on a Six Sigma project that used other methodologies, as Performance Measurement System, Balanced Scorecard, Benchmarking and Process Management, to increase the efficiency of the logistics of the company. The obstacles found in the implementation of the performance indicators were very inferior to the significant improvements, demonstrating that there is a positive trade off.